POTENSI PENGEMBANGAN GEOWISATA UNTUK MENDUKUNG PERWUJUDAN GEOPARK GALUNGGUNG KABUPATEN TASIKMALAYA - Fatma Fadillah; Azrina Ruhiati Rahman; Dephew Nadya Caroline (Jurnal Pariwisata Tawangmangu, 2026)
This study aims to analyze the potential for geotourism development in the Galunggung Geopark area. Tasikmalaya Regency supports conservation, education, and sustainable economic growth. The research employed a qualitative approach, using literature review methods to examine relevant scientific sources and documents. The results indicate that the Galunggung area has significant geotourism potential through diverse geosites such as Galunggung Crater, Telaga Bodas, and Cipanas Hot Springs, as well as cultural attractions like Kampung Naga. The three main pillars of geopark conservation, education, and community-based economic empowerment can be integrated to strengthen the geopark's tourism value. However, challenges remain in terms of infrastructure and local human resource capacity. Therefore, collaboration among local governments, educational institutions, and local communities is essential to realize Galunggung Geopark as a sustainable and environmentally conscious geotourisn destination.